Curing the highcost-syndrome - Abd Razak, Dzulkifli (2006)
The Health Ministry's announcement last week that it is working on a proposal to cap the prices of more than 1,000 essential medicines is welcome, though the move is long overdue. For a long time, the question of drugs has been a bone of contention between Malaysian health activists and consumers. The last time Malaysia discussed this issue was almost a decade ago but it was of little avail. Maybe this time it will be different. A survey recently (NST, May 9) showed that many Malaysians pay exorbitant prices for their medicines. In fact, drug prices in Malaysia are far above the international reference pricing, a guide on how much medicine should cost. The ministry's list of essential medicines will include antibiotics, aspirin and other painkillers, as well as medicines for high blood pressure and depression.